1986
DOI: 10.1159/000180298
|View full text |Cite
|
Sign up to set email alerts
|

Role of 5-Hydroxytryptamine in the Regulation of Brain Neuropeptides in Normal and Diabetic Rat

Abstract: The effect of 5-hydroxytryptamine (5-HT) alteration on brain dopamine (DA), norepinephrine (NE), β-endorphin (βE) and immunoreactive insulin (IRI) was studied in Sprague-Dawley diabetic and control rats. Diabetes was induced using alloxan (45 mg/kg), 15 days prior to sacrificing. Both control and diabetic animals were treated with either p-chlorophenylalanine (PCPA, 300 mg/kg) 3 days prior to sacrificing or fluoxetine (10 mg/kg) twice daily for 3 days. PCPA treatment significantly decreased brain content of 5-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
12
0

Year Published

1987
1987
2005
2005

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 29 publications
2
12
0
Order By: Relevance
“…Furthermore, in streptozotocin-treated rats, a decrease in fl-endorphin content in the hypothalamus and neurointermediate lobe of the pituitary has been reported (Forman et al 1985(Forman et al , 1986. A similar decrease in brain content of fl-endorphin has also been reported in alloxan-induced diabetes (Kolta et al 1986). Therefore, attentuation of the naloxone response observed in our study in streptozot0cin-treated animals can be explained on the basis of a decrease in the level of endogenous opioid peptides.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, in streptozotocin-treated rats, a decrease in fl-endorphin content in the hypothalamus and neurointermediate lobe of the pituitary has been reported (Forman et al 1985(Forman et al , 1986. A similar decrease in brain content of fl-endorphin has also been reported in alloxan-induced diabetes (Kolta et al 1986). Therefore, attentuation of the naloxone response observed in our study in streptozot0cin-treated animals can be explained on the basis of a decrease in the level of endogenous opioid peptides.…”
Section: Discussionmentioning
confidence: 59%
“…Moreover, it is well known that feeding of a carbohydrate-rich diet is associated with an increase in the brain level of 5HT (Crandall and Fernstrom 1980;Chiel and Wurtman 1981). Previously, we have found that induction of diabetes in the rat was associated with an elevated brain 5HT level (Kolta et al 1986). The potentiating effect of sympathomimetic amines such as d-amphetamine on opioid antinociceptive activity has been observed in mice (Dewey et al 1970) and humans (Forrest et al 1977).…”
Section: Discussionmentioning
confidence: 85%
“…More recently, the alpha adrenergic agonist clonidine and morphine were shown to potentiate each other in the mouse tail flick test (Spaulding et al 1979). There is also evidence that an elevated level of 5HT is associated with the release offl-endorphin (Kolta et al 1986;Soliman et al 1986). Accumulation and release of antagonistic peptides in the brain, such as ACTH and MStt, might play an important role in the mechanism of opiate tolerance and withdrawal syndrome (Gessa et al 1983).…”
Section: Discussionmentioning
confidence: 99%
“…Diabetes mellitus is accompanied by several psychicontent of their metabolites, and alterations in monoamine receptor density have been reported (Crandall et al, 1981;Lozovsky et aI., 1981;Trulson and Himmel, 1985;Kolta et al, 1986;Trulson et al, 1986;Bitar and Desouza, 1990;Salkovié and Lackovié, 1992). Changes are restricted to a few brain regions, often seen in the striatum and the hypothalamus, with different time courses of appearance (Bitar et al, 1985;Chu et al, 1986;Oliver et al, 1989;Salkovié and Lackovié, 1992;Ramakrishnan and Namasivayam, 1995).…”
mentioning
confidence: 96%